Use the method of reduction of order to find a second solution to t^2y' + 3ty' – 3y = 0, t> 0 Given yı(t) = t y2(t) = Preview Give your answer in simplest form (ie no coefficients)

Respuesta :

Let [tex]y_2(t)=tv(t)[/tex]. Then

[tex]{y_2}'=tv'+v[/tex]

[tex]{y_2}''=tv''+2v'[/tex]

and substituting these into the ODE gives

[tex]t^2(tv''+2v')+3t(tv'+v)-3tv=0[/tex]

[tex]t^3v''+5t^2v'=0[/tex]

[tex]tv''+5v'=0[/tex]

Let [tex]u(t)=v'(t)[/tex], so that [tex]u'(t)=v''(t)[/tex]. Then the ODE is linear in [tex]u[/tex], with

[tex]tu'+5u=0[/tex]

Multiply both sides by [tex]t^4[/tex], so that the left side can be condensed as the derivative of a product:

[tex]t^5u'+5t^4u=(t^5u)'=0[/tex]

Integrating both sides and solving for [tex]u(t)[/tex] gives

[tex]t^5u=C\implies u=Ct^{-5}[/tex]

Integrate again to solve for [tex]v(t)[/tex]:

[tex]v=C_1t^{-6}+C_2[/tex]

and finally, solve for [tex]y_2(t)[/tex] by multiplying both sides by [tex]t[/tex]:

[tex]tv=y_2=C_1t^{-5}+C_2t[/tex]

[tex]y_1(t)=t[/tex] already accounts for the [tex]t[/tex] term in this solution, so the other independent solution is [tex]y_2(t)=t^{-5}[/tex].

ACCESS MORE